A note on "A new fuzzy regression model based on absolute deviation". (November 2017) - Al-Qudaimi, Abdullah; Kumar, Amit
Abstract: Li et al. (2016) proposed a least absolute deviation method to find such fuzzy regression models whose all the parameters are trapezoidal fuzzy numbers. Since, the method, proposed by Li et al., is published in Engineering Applications of Artificial Intelligence (a very reputed International Journal) as well as it is easy to apply Li et al. method in real life problems. So, other researchers may be attracted to apply the method, proposed by Li et al., to find the solution of real life problems. However, after a deep study of the work done by Li et al., it is noticed that the multiplication of two trapezoidal fuzzy numbers, proposed by Li et al. as well as used in this method, is not valid. Hence, the aim of this note is to make the researchers aware about the valid multiplication of trapezoidal fuzzy numbers that should be used in Li et al. method.